James Watson Cronin. 29 September 1931 — 25 August 2016. (12th December 2018) - Watson, Alan
Abstract : James (Jim) Cronin had two outstanding careers. The first, in particle physics, included the discovery of CP violation for which he and Val Fitch were awarded the Nobel Prize in 1980. During the second, in cosmic rays, he played a major role in raising the profile of that field, particularly through his leadership in the creation of the Pierre Auger Observatory, the largest cosmic-ray detector ever constructed. He will be remembered for his incisive mind, his modest style, his internationalism and his encouragement of young scientists, as well as for his brilliance as an experimental physicist and data analyst.